A lateral–torsional buckling demonstration model using 3D printing. (1st April 2023) - Virgin, L.N.; Harvey, P.S.
Abstract: It is well-established that beams of relatively narrow cross-section have a tendency to buckle laterally when loaded. This type of lateral–torsional instability, which has considerable practical importance in a variety of thin-walled structures, is a classical buckling situation in which the critical load is related, among other things, to characteristic features of the cross-section. In this short paper, 3D-printing is exploited to provide a parametric study based on a fixed cantilever geometry in which a number of standard cross-sectional forms are compared in terms of their effect on this kind of buckling behavior. Highlights: Innovative use of 3D printing. Lateral–torsional buckling (LTB). Experimental testing. A practical enhancement of teaching LTB.